AN ASSUMED STRAIN BASED ON TRIANGULAR ELEMENT WITH DRILLING ROTATION - BELARBI, M.T.; BOUREZANE, M. (Courrier du Savoir, 2014)
The lack of compatibility betweendegrees of freedom of various elements isa problem frequently encountered in practice during modeling complex structures. Coupling of membrane and beam elements is an illustrating classical example. The problem is generally treated through an additional rotational degree of freedom [1]. In this respect a new element based on the strain field has been developed with a drilling rotation in the Bergan sense [2]. The triangular element, with three nodes and three degrees of freedom constructed in this way, presentsvery good performance and may be used in various practical problems.